2019
DOI: 10.1037/emo0000438
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes and prejudice affect the recognition of emotional body postures.

Abstract: Most research on emotion recognition focuses on facial expressions. However, people communicate emotional information through bodily cues as well. Prior research on facial expressions has demonstrated that emotion recognition is modulated by top-down processes. Here, we tested whether this top-down modulation generalizes to the recognition of emotions from body postures. We report three studies demonstrating that stereotypes and prejudice about men and women may affect how fast people classify various emotiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
30
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 54 publications
7
30
2
Order By: Relevance
“…Finally, the present research has implications for experimental design. Our studies converge with the idea that the task context is crucial in activating stereotype or evaluative associations (Bijlstra et al, 2010(Bijlstra et al, , 2018Wittenbrink et al, 2001). The kind of expectations that people use, either evaluation-or stereotype-based expectations, depend on whether valence differences are salient within the context.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…Finally, the present research has implications for experimental design. Our studies converge with the idea that the task context is crucial in activating stereotype or evaluative associations (Bijlstra et al, 2010(Bijlstra et al, , 2018Wittenbrink et al, 2001). The kind of expectations that people use, either evaluation-or stereotype-based expectations, depend on whether valence differences are salient within the context.…”
supporting
confidence: 82%
“…Stereotype associations have only been found to affect emotion recognition when emotions in a recognition task do not differ in valence, i.e. two negative emotional expressions (single-valence conditions; Bijlstra et al, 2010;Bijlstra, Holland, Dotsch, Hugenberg, & Wigboldus, 2014;Bijlstra, Holland, Dotsch, & Wigboldus, 2018). This is illustrated in our previous work (Bijlstra et al, 2010) by participants' recognition speed regarding sad male and female faces.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Finally, we took the sex of the child being observed into account. Research has shown that in men, sadness, angry facial expressions are more easily recognized (Bijlstra et al, 2010), whereas in women positive emotions and body postures are more easily recognized (Bijlstra et al, 2010;Bijlstra et al, 2019). It is therefore possible that judges are more likely to see negative behavior in boys, and positive social behavior in girls, affecting the accuracy of their judgment.…”
Section: Social Characteristics Of the Child Being Judgedmentioning
confidence: 99%